Arsenic in Portuguese Rice: Is There Any Risk? - Silva, Alexandra (2022)
Arsenic is a metalloid with natural and anthropogenic sources and its inorganic form is toxic to humans. Rice is highly consumed worldwide and is prone to arsenic contamination; therefore, this study evaluated the inorganic arsenic content of 70 Portuguese rice samples. These were analysed through inductively coupled plasma mass spectrometry (ICP-MS) with a detection limit of 3.3 µg kg-1. The average contamination was of 29.3 µg kg-1, with brown and short rice presenting higher values than white and long rice. The highest concentration, 100 µg kg-1, equalled the maximum residue limit (MRL) for rice destined for infants' consumption. The estimated daily intake (EDI) surpassed the benchmark dose (lower confidence limit 10%) (BMDL10) of 0.3 µg kg-1 of bw/day considering children in the 95th percentile of rice consumption and the worst-case scenario concentration. However, other sources also contribute to the EDI and some population groups can exceed the BMDL10.